Correction: Development of P3-K0.69CrO2 as an ultra-high-performance cathode material for K-ion batteries. Issue 9 (1st August 2018) - Hwang, Jang-Yeon; Kim, Jongsoon; Yu, Tae-Yeon; Myung, Seung-Taek; Sun, Yang-Kook
Abstract : Correction for 'Development of P3-K0.69 CrO2 as an ultra-high-performance cathode material for K-ion batteries' by Jang-Yeon Hwang et al., Energy Environ. Sci., 2018, DOI: ;10.1039/c8ee01365a .